2001
DOI: 10.1002/hed.10009
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of c‐jun and c‐fos mRNAs in squamous cell carcinoma of the head and neck: Associations with uPA, gelatinase B, and matrilysin mRNAs

Abstract: Expression of c-jun seems to be involved in the regulation of gelatinase B and matrilysin being not related to uPA. Lack of association with c-fos may indicate that other fos family members might play a role in the transcriptional activity of the analyzed proteases in HNSCC tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 45 publications
(18 reference statements)
4
21
0
1
Order By: Relevance
“…C-fos plays pivotal role in the regulation of cell growth and differentiation. Over expression of c-fos was reported in several cancers including cervical cancer, lung cancer, pancreatic carcinomas, osteosarcomas, hepatocellular carcinoma and colorectal adenoma (Pacheco et al, 2002;Petrov et al, 1994). Over expression of c-fos was reported in 70% and 38% of the oral cancers and oral pre-cancerous lesions respectively (Vairaktaris et al, 2008;Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…C-fos plays pivotal role in the regulation of cell growth and differentiation. Over expression of c-fos was reported in several cancers including cervical cancer, lung cancer, pancreatic carcinomas, osteosarcomas, hepatocellular carcinoma and colorectal adenoma (Pacheco et al, 2002;Petrov et al, 1994). Over expression of c-fos was reported in 70% and 38% of the oral cancers and oral pre-cancerous lesions respectively (Vairaktaris et al, 2008;Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…MMP3 and MMP7 expression levels are documented in HNSCC as in other epithelial tumor types. Moreover, increased expression in normal surrounding tissue has been documented for MMP3, underlying the importance of matrix components on tumor progression (15,27). MMP3 is expressed at very low levels in normal adult tissues, and peritumoral expression could be because the host tissue reacted as though the tumor was a wound.…”
Section: Discussionmentioning
confidence: 99%
“…2002) and none focused all members of jun–fos family. Our own previously published data indicated that c‐Jun mRNA was differentially expressed in HNSCC, compared to that in adjacent normal tissue, and correlated with the expression of uPA mRNA, implicating in a possible role of these factors in invasion (Pacheco et al . 2002).…”
mentioning
confidence: 93%
“…Concerning head and neck tumours, few studies had examined AP‐1 expression (Ondrey et al . 1999; Pacheco et al . 2002; Serewko et al .…”
mentioning
confidence: 99%